Report of the Working Group on Wildlife Ecotourism and Animal Welfare for the 12th Five Year Plan 2012-2017 - Planning Commission (Planning Commission, 2011)
India is uniquely blessed with wildlife diversity. One of eighteen mega diverse countries, it is home to 7.6% of all mammalian, 12.6% of all avian, 6.2% of all reptilian, 4.4% of all amphibian, 11.7% of all fish, and 6.0% of all flowering plant species. This diversity becomes even more remarkable given that our country, with only 2.4 per cent of the total land area of the world, contributes 8 per cent to the known global biological diversity, while also being the second largest populous nation in the world, with over 1.2 billion people.
Planning Commission, Government of India